Stresses, Temperature and Oscillations of Thermoelastic Layer Suddenly Exposed to Symmetric Pressure - Marjanov, M.M. (Engineering Transactions, 1980)
In the Principles of Thermoelasticity [1], KOVALENKO presented the limit values of temperature increase in a thermoelastic layer, exposed to a symmetric step in time pressure. This work treats the same problem. The approximate solutions are found for temperature, stresses and displacements in function of time and space variable.